2012
DOI: 10.1128/jb.06603-11
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Genome Project for the Aromatic Degrader Rhodococcus pyridinivorans Strain AK37

Abstract: Here, we present the complete genome sequence of Rhodococcus pyridinivorans AK37 strain NCAIM PB1376, which was isolated from an oil-polluted site in Hungary. R. pyridinivorans AK37 is an aerobic, nonsporulating, nonmotile, Gram-positive bacterium with remarkable aromatic-decomposing activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Molecules 2020, XX, x FOR PEER REVIEW 5 of 18 microorganisms reflects the fact that other energy sources are more prevalent in the environment. However, especially for the main crude oil ingredients, aliphatic and monoaromatic hydrocarbons [21,22], well-regulated and fine-tuned catabolic pathways are already present, reflecting their longexisting occurrence in the evolution when compared to "new" developed catabolic genes and operons, respectively, encoding for only quite recently applied chemicals such as pesticides (e.g., atrazine) or chlorinated hydrocarbons (e.g., highly chlorinated phenols and biphenyls) [23,24]. There are, however, exceptions to the statement given above-bacterial blooms following oil spills.…”
Section: To Biodegrade or Not To Biodegrade?mentioning
confidence: 99%
“…Molecules 2020, XX, x FOR PEER REVIEW 5 of 18 microorganisms reflects the fact that other energy sources are more prevalent in the environment. However, especially for the main crude oil ingredients, aliphatic and monoaromatic hydrocarbons [21,22], well-regulated and fine-tuned catabolic pathways are already present, reflecting their longexisting occurrence in the evolution when compared to "new" developed catabolic genes and operons, respectively, encoding for only quite recently applied chemicals such as pesticides (e.g., atrazine) or chlorinated hydrocarbons (e.g., highly chlorinated phenols and biphenyls) [23,24]. There are, however, exceptions to the statement given above-bacterial blooms following oil spills.…”
Section: To Biodegrade or Not To Biodegrade?mentioning
confidence: 99%
“…Such behavior has been mostly related to changes in the cell wall, that hinders the diffusion of deleterious compounds; or to the metabolic versatility displayed by members of this genus, which result in the partial or total mineralization of the toxic compounds or proper processing for use as carbon and/or energy source (Larkin et al, 2005 ; de Carvalho et al, 2005 , 2009 ; de Carvalho, 2012 ). Although active transport is a well-known tool for microbial strains to deal with toxic compounds (Torres et al, 2011 ; Kriszt et al, 2012 ; Nikaido and Pagès, 2012 ; Segura et al, 2012 ) there are very few works where this method has been clearly identified in Rhodococcus strains despite this possibility is often suggested. Such exceptions include: (a) the selective transport of n-hexadecane by R. erythropolis S+14He (Kim et al, 2002 ).…”
Section: Transport Of Solvents Antibiotics and Biocidesmentioning
confidence: 99%
“…Bacterial species belonging to the genus Rhodococcus possess the ability to degrade a large diversity of xenobiotic and organic compounds (aliphatic, aromatic, and alicyclic hydrocarbons) that are usually present in polluted soil or oil spills ( 1 3 ). These are also suggested to be involved in the metabolism of steroids and atrazine compounds ( 4 , 5 ). Strains of Rhodococcus pyridinivorans , like SB3094, have the ability to degrade methyl-ethyl-ketone (MEK) and thus have been used for bioaugmentation relating to the treatment of wastewater contamination by petrochemical hydrocarbons ( 6 ).…”
Section: Genome Announcementmentioning
confidence: 99%